2009
DOI: 10.1097/inf.0b013e3181aa6411
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Outcome of Surgical Excision Versus Antibiotic Therapy for Nontuberculous Mycobacterial Cervicofacial Lymphadenitis in Children

Abstract: One hundred children with microbiologically proven nontuberculous mycobacterial cervicofacial lymphadenitis were randomly assigned to excision of the involved lymph nodes, or antibiotic therapy consisting of clarithromycin and rifabutin. The esthetic outcome was rated using a revised and weighted Observer Scar Assessment Scale. The median weighted esthetic outcome in surgical patients was significantly better (30.6) than that for patients treated with antibiotics (42.2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 9 publications
0
27
1
3
Order By: Relevance
“…The most common manifestation of M. haemophilum infection in immunocompetent children is cervicofacial lymphadenitis. Excisional surgery leads to a quick resolution and the best esthetic outcome (87,88). In more advanced stages with extensive necrosis and skin discoloration, excisional surgery can be technically difficult.…”
Section: Immunocompetent Patientsmentioning
confidence: 99%
“…The most common manifestation of M. haemophilum infection in immunocompetent children is cervicofacial lymphadenitis. Excisional surgery leads to a quick resolution and the best esthetic outcome (87,88). In more advanced stages with extensive necrosis and skin discoloration, excisional surgery can be technically difficult.…”
Section: Immunocompetent Patientsmentioning
confidence: 99%
“…In the observational series of Zeharia et al (4), showing good results with observation alone, 90% of cases of lymphadenitis were caused by Mycobacterium haemophilum, probably reflecting the local environmental mycobacterial flora. In a study by Lindeboom et al (25), M. haemophilum was also a dominant pathogen. It is possible that M. haemophilum infections would heal more readily than those caused by MAC, which is known to possess a higher differential pathogenicity and caused the majority of infections among our patients (26).…”
Section: Discussionmentioning
confidence: 95%
“…In a study by Lindeboom et al. (25), M. haemophilum was also a dominant pathogen. It is possible that M. haemophilum infections would heal more readily than those caused by MAC, which is known to possess a higher differential pathogenicity and caused the majority of infections among our patients (26).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Randomized trials have demonstrated that surgical excision produces superior cure rates and esthetic outcomes to medical therapy. 113,114 Excision may be complicated by permanent paralysis of the marginal mandibular branch of the facial nerve. Surgical curettage may be an alternative to surgical excision in cases with necrotic nodes adherent to the facial nerve, although healing times are longer.…”
Section: Cervicofacial Adenitismentioning
confidence: 99%